1983
DOI: 10.1177/1077727x8301200208
|View full text |Cite
|
Sign up to set email alerts
|

Mother's Time on Meal Preparation, Expenditures for Meals Away from Home, and Shared Meals: Effects of Mother's Employment And Age of Younger Child

Abstract: Family role theory is the framework used to guide this study of how mother's employment and age of younger child affects mother's time in meal preparation and cleanup, expenditures for meals away from home, and meals shared by the family both at home and away. Eleven null hypotheses are generated and tested using data from the 11 state urban/rural comparison of families' time use. Analysis of covariance (with total family income controlled) is the primary statistical tech nique employed. Results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…On the basis of previous research (e.g., Fletcher, 1981;Senauer, Sahn, & Alderman, 1986), conditioned on data availability (i.e., it was not possible to estimate the time value of individuals who were not household heads), (Tobin, 1958) Similar results were obtained by Goebel and Hennon (1983) in their analysis, which included only two-parent, two-child households. Fletcher (1981) found that income, the value of the household's time, and the composition of the household influence the household's life cycle expenditures for FAFH, all consistent with the results of the present study.…”
Section: Methodsmentioning
confidence: 52%
“…On the basis of previous research (e.g., Fletcher, 1981;Senauer, Sahn, & Alderman, 1986), conditioned on data availability (i.e., it was not possible to estimate the time value of individuals who were not household heads), (Tobin, 1958) Similar results were obtained by Goebel and Hennon (1983) in their analysis, which included only two-parent, two-child households. Fletcher (1981) found that income, the value of the household's time, and the composition of the household influence the household's life cycle expenditures for FAFH, all consistent with the results of the present study.…”
Section: Methodsmentioning
confidence: 52%
“…While the evidence is not unambiguous, and there is a need for a more comprehensive empirical database, research within the US suggests that the breakdown in family meal structures appears to be most advanced in situations where both the male and female work (Goebel and Hennon 1983;Siega-Riz 1998). However, these linkages are complex in that higher levels of female employment in many states in continental Europe have not had the same severity of impact on meal structures.…”
Section: Iain Piriementioning
confidence: 88%
“…Analyzing the conversation during a family meal is also important for culture studies [4]. Moreover, it is shown that, by reviewing detailed activity logs, people are motivated to modify their behaviors toward a healthy lifestyle [11][6][13][12]. …”
Section: Motivation and Requirementsmentioning
confidence: 99%
“…In addition to the implications for family health, fine-grained analysis of family mealtime enables important studies in sociology and home economy. For instance, research has showed that the amount of shared time (including conversation and eating) between spouses and between parents and children have strong links with family income, mother’s employment status, ages of children, and geographic location (urban or rural) [6][13][12]. However, according to a national survey in 2014, American families with children on an average work day spend almost 3 hours watching TV accounting for more than half of the leisure and sport time, while only 1 hour for family meal [24].…”
Section: Introductionmentioning
confidence: 99%